Constitutional Perspectives on the Enforcement of Socio-Economic Rights: Recent South African Experiences - Olivier, Marius (Victoria University of Wellington Law Review, 2002)
The forging of South Africa’s constitution and Bill of Rights in 1996 was undoubtedly an important historic event. This paper presents a fascinating discussion concerning the treatmentand methodology employed by South African Constitutional Courts in interpreting theConstitution and its Bill of Rights. Particular attention is paid to the far-reaching judgment by theConstitutional Court in Government of the Republic of South Africa v Grootboom. Inconcluding, this paper develops a non-exhaustive list of guiding principles developed from theCourt’s approach.